Social Media and Its Impact on the Use of English Borrowings in Indonesian - Dini Adriani; Sri Endah Tabiati; Esti Junining (Universitas Brawijaya, 2018)
As social media increasingly became a lifestyle of the Indonesians in responding to popular phenomena, social media has become daily needs. On the other side, the use of English borrowings in Indonesian increases in terms of quantity and frequency. This research aims at investigating the correlation between social media access intensity and the use of English borrowings in Indonesian. This study is designed to investigate whether there is a correlation between social media access intensity and the use of English borrowings by Indonesian people aged 18 to 34. The design of this research is a correlation. The population of the study was Indonesian social media users aged 18 to 34 (N=196). Snowball sampling was employed to decide samples of study. In order to get the data, this study used the questionnaire as an instrument. There is a significant correlation between social media access intensity and the use of English borrowings in Indonesian r = .286, p<0.05.